Segregating the Chickenheads: Philip K. Dick's Do Androids Dream of Electric Sheep? and the Post/humanism of the American Eugenics Movement - Pottle, Adam (Disability Studies Quarterly, 2013)
This essay reads Philip K. Dick's novel Do Androids Dream of Electric Sheep? as a critique of the American eugenics movement. Replete with historical allusions and satiric wordplay, Dick's novel condemns the eugenics movement as eliminating disability, diminishing human diversity, discouraging empathy, and ushering in harmful posthuman ideas before their time. Keywords: Eugenics; Philip K. Dick; America; Science fiction; Do Androids Dream of Electric Sheep